Short communicationPTSD symptoms of survivors of an airline event in Teheran - Mirzamani, Seyed-Mahmoud; Mohammadi, Mohammad Reza (Archives of Medical Science, 2007)
Introduction: This study investigated the PTSD symptoms of 39 survivors of a 2005 airline crash in Tehran. Material and methods: The 39 participants ranged in age from 17 to 70 years. The mean age of participants was 33.8 (standard deviation 14.5). The assessment measures used were the Posttraumatic Stress Disorder Symptom Scale (PSS) and clinical interviews based on the DSM-IV-TR. Results: Twenty-six participants (66.7%) were diagnosed with PTSD using the PSS and 29 (74.4%) were diagnosed with PTSD by psychiatric interview. Conclusions: There must be more aftermath care, treatment and social support for survivors in Iran and all other countries.